Diverse interactions of Mycobacterium tuberculosis infection and of BCG vaccination with SARS-CoV-2 - Salgame, Padmini; Pentakota, Sri Ram; Malabad, John Carlo M.; Narasimhan, Prakash Babu; Verma, Sheetal; Prakash Babu, Senbagavalli; Sharma, Vartika; Sarkar, Sonali; Alejandria, Marissa M.; Ellner, Jerrold J. (Frontiers in Tuberculosis, 2024)
The COVID pandemic and tuberculosis (TB) endemicity is double trouble to much of the world. SARS-CoV-2 and Mycobacterium tuberculosis (Mtb), causative agents of COVID and TB, respectively, are both infectious respiratory pathogens involving close communities and individuals. Both pathogens can cause lung disease, involving unbalanced inflammatory cell immune responses that can lead to a syndemic impact. Moreover, dual infection is common in certain settings. In low-and middle-income countries, most individuals with SARS-CoV-2 infection or COVID-19, in fact, will have been exposed to or infected with Mtb and some will develop active TB. Here we review the literature examining the diverse interactions of M. tuberculosis infection and of BCG vaccination with SARS-CoV-2. We discuss areas in which contradictory results have been published and conclude that there are still several unresolved issues that warrant further study on the co-pathogenesis of SARS-CoV-2 and Mtb and BCGmediated heterologous protection against COVID-19.